East London Project: a participatory mixed-method evaluation on how removing enforcement could affect sex workers' safety, health and access to services in East London - Pippa Grenfell; Jocelyn Elmes; Rachel Stuart; Janet Eastham; Josephine Walker; Chrissy Browne; Carolyn Henham; M Paz Hernandez Blanco; Kathleen Hill; Sibongile Rutsito; Maggie O’Neill; MD Sarker; et al. (Public Health Research)
Background Sex workers’ risk of violence and ill-health is shaped by their work environments, community and structural factors, including criminalisation. Aim We evaluated the impact of removing police enforcement on sex workers’ safety, health and access to services. Design Mixed-methods participatory study comprising qualitative research, a prospective cohort study, mathematical modelling and routine data collation. Setting Three boroughs in London, UK. Participants People aged ≥ 18 years, who provided in-person sexual services. Interventions Simulated removal of police enforcement. Outcomes Primary – recent or past experience of sexual, physical or emotional violence. Secondary – depression/anxiety symptoms, physical health, chlamydia/gonorrhoea, and service access. Results A combination of enforcement by police, local authorities and immigration, being denied justice when reporting violence, and linked cuts to specialist health and support services created harmful conditions for sex workers. This disproportionately affected cisgender and transgender women who work on the streets, use drugs, are migrants and/or women of colour. Among women (n = 197), street-based sex workers experienced higher levels than indoor sex workers of recent violence from clients (73% vs. 36%), police (42% vs. 7%) and others (67% vs. 17%); homelessness (65% vs. 7%); anxiety and depression (71% vs 35%); physical ill-health (57% vs 31%); and recent law enforcement (87% vs. 9%). For street-based sex workers, recent arrest was associated with violence from others (adjusted odds ratio (AOR)) 2.77, 95% confidence interval (CI) 1.11 to 6.94). Displacement by police was associated with client violence (AOR 4.35; 95% CI 1.36 to 13.90) as were financial difficulties (AOR 4.66; CI 1.64 to 13.24). Among indoor sex workers, unstable residency (AOR 3.19; 95% CI 1.36 to 7.49) and financial difficulties (AOR 3.66; 95% CI 1.64 to 8.18) contributed to risk of client violence. Among all genders (n = 288), ethnically and racially minoritised sex workers (26.4%) reported more police encounters than white sex workers, partly linked to increased representation in street settings (51.4% vs. 30.7%; p = 0.002) but associations remained after adjusting for work setting. Simulated removal of police displacement and homelessness was associated with a 71% reduction in violence (95% credible interval 55% to 83%). Participants called for a redirection of funds from enforcement towards respectful, peer-led services. Limitations Restriction to one urban locality prevents generalisability of findings. More interviews with under-represented participants (e.g. trans/non-binary sex workers) may have yielded further insights into inequities. Correlation between different risk factors restricted outcomes of interest for the modelling analyses, which were largely limited to experience of violence. Conclusion Our research adds to international evidence on the harms of criminalisation and enforcement, particularly for women who work on street and/or are racially or ethnically minoritised. Findings add weight to calls to decriminalise sex work, tackle institutionally racist, misogynist and otherwise discriminatory practices against sex workers in police and other agencies, and to (re)commission experience-based, peer-led services by and for sex workers particularly benefiting the most marginalised communities. Future work Realist informed trials, co-produced with sex workers, would provide rigorous evidence on effective approaches to protect sex workers’ health, safety and rights. Funding This synopsis presents independent research funded by the National Institute for Health and Care Research (NIHR) Public Health Research programme as award number 15/55/58. Plain language summary Some sex workers experience greater levels of violence, anxiety, depression and drug use than people who do not sell sex. This research evaluated the effects of removing police enforcement on sex workers’ safety and health (violence, depression and anxiety) and access to health and social care in East London. The study was participatory: co-researchers with lived experience of sex work or of working closely with sex workers worked with university-based researchers to design, conduct and disseminate the research. We conducted qualitative research (interviews and neighbourhood walks) to understand how police enforcement affected sex workers’ safety, health and service access. We measured how much enforcement affected levels of violence, through a cohort study (recruiting participants and following up with them over time). We then developed a mathematical model to simulate the effects of removing enforcement. In this urban locality, we found that women (cisgender and transgender) who worked on the street experienced far higher levels of police enforcement and reported more violence from all perpetrators, including police themselves, than those working indoors. They reported higher levels of anxiety and depression and were less likely to be getting help for these problems. In our study, sex workers’ safety and mental health were affected by entrenched poverty, insecure housing, police enforcement and service cuts. Cisgender and transgender women who worked on the street, used drugs, were migrants and/or were women of colour were particularly targeted for enforcement, denied justice and affected by funding cuts to specialist health and support services. Ethnically and racially minoritised sex workers more frequently worked in lower-paid, street-based settings and, regardless of work setting, were more frequently arrested and imprisoned. Our mathematical modelling suggested that stopping the displacement of street-based sex workers alongside the provision of housing could result in a significant (71%) reduction in client violence. Participants recommended redirecting funds from enforcement towards respectful, peer-led services. Findings add weight to existing international evidence on ending enforcement against sex workers and the need to address other of violence and poor health, including reducing poverty, providing housing and commissioning appropriate, community-led services for sex workers.